Clinical, Haemato-biochemical Evaluation and Comparison of Polymerase chain reaction with Conventional Blood Smear Examination for the Detection of Babesia gibsoni Infection in Dogs - Sai, Peddineni Sree Krishna; Vijayalakshmi , P; Abiramy , @ Prabavathy A; Devadevi , N; Rajkumar, K; ratnam, D Himaja Satya Sai (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of the present study was to detect Babesia gibsoni infection in dogs which are presented to Veterinary Clinical Complex, Rajiv Gandhi Institute of Veterinary Education and Research, Puducherry. A total of 85 dogs with clinical signs such as inappetence, fever, enlarged lymph nodes and tick infestation were screened. The diagnostic efficacy of polymerase chain reaction (PCR) technique has been compared with blood smear examination to detect B. gibsoni infection in dogs. By   blood smear and PCR examination, six (7.1%) dogs and 28 (42.4%) dogs were positive for B. gibsoni infection respectively. Clinical examination of dogs with B. gibsoni showed tick infestation, anorexia, dullness, pyrexia, pale/congested conjunctival mucus membrane, tachypnoea and swollen lymph nodes. In addition, few dogs had icterus and haemoglobinuria. Laboratory examination of blood samples of B. gibsoni dogs revealed significant reduction in haemoglobin, PCV, erythrocyte count, platelet count and serum albumin levels. Significant increase in levels of ALP, globulin, bilirubin, BUN and creatinine were recorded.
Keywords: Babesia gibsoni; PCR; blood smear examination; dogs